Heritability, Genetic Advance and Correlations in 254 Maize Doubled Haploid Lines × Tester Crosses under Drought Conditions - A. M. M. Al-Naggar; A. M. A. Abdalla; A. M. A. Gohar; E. H. M. Hafez (Archives of Current Research International, 2016)
One of the major advantages of doubled haploid lines (DHL) is the maximum genetic variance between lines for testcross performance from the first generation. Two hundred fifty four testcrosses were produced as a result of crossing between 254 DHL’s and an inbred line tester. The objectives were: (i) to determine the genotypic (GCV) and phenotypic (PCV) coefficients of variation, heritability (h2b) and genetic advance (GA) from selection under water stressed at flowering (WSF) and grain filling (WSG) and under well-watered (WW) and (ii) to identify the traits of significant correlation with grain yield under water stressed environments. A split plot design in lattice (16 x 16) arrangement was used with two replications, where three irrigation treatments (WW, WSF and WSG) were allotted to main plots and genotypes (254 top crosses) to sub-plots. A separate analysis of variance of RCBD was also performed under each irrigation treatment for estimating the genetic parameters. The PCV and GCV estimates were high for plant height (PH), ear height (EH) and grain yield/plant (GYPP), low for other studied traits, except for barren stalks (BS) which was of medium magnitude. The highest h2 estimate (>90%) was exhibited by days to anthesis (DTA), days to silking (DTS), PH, EH and leaf rolling (LR) under all environments and anthesis silking interval (ASI) under WW, while the lowest h2 estimate (< 46%) was shown by BS and ears plant-1 (EPP) traits. For DTA, DTS, BS, EPP, GYPP and grain yield/ha (GYPH) traits, heritability was increased in stressful environments (WSF or WSG), while for ASI and LR, the opposite was true. The highest GA (>30%) was shown by PH followed by EH and GYPP, while the lowest GA (<1%) was shown by EPP. The best selection environment for GYPP and GYPH was the stressed one (WSF or WSG). GYPH or GYPP of top crosses showed significant and negative genetic correlations with DTA, DTS, ASI, BS and LR and significant positive correlations with EPP and PH in all environments.